The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.13057/biodiv/d190402
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of trees species in Tripa Peat Swamp Forest, Aceh, Indonesia inferred by 5.8S nuclear gen

Abstract: Authors. 2018. Molecular phylogeny of trees species in Tripa Peat Swamp Forest, Aceh, Indonesia inferred by 5.8S nucleargen. Biodiversitas 19: 1186-1193. Tripa peat swamp forest is protected areas that have high biodiversity. Nevertheless, in some areas,the damage occurred due to conversions of land function to oil palm plantations. The impact of conversions of peat swamp forest to oilpalm plantations has led to biodiversity decreased. Hence, it is important to identify the remain tree species in Tripa peat sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…These species are: S. caudatilimbum, S. chloranthum and T. Obovata. Almost similar with this finding, Thomy et al (2018) and Yulisma et al (2018) reported that the most dominant species in Tripa peat swamp forest, Aceh have also belonged to Myrtaceae and Dipterocarpaceae. The dominant presence of Myrtaceae members may be related to their genetic and adaptability factors (Yulisma et al 2018).…”
Section: Diversity Of Plant Speciessupporting
confidence: 84%
“…These species are: S. caudatilimbum, S. chloranthum and T. Obovata. Almost similar with this finding, Thomy et al (2018) and Yulisma et al (2018) reported that the most dominant species in Tripa peat swamp forest, Aceh have also belonged to Myrtaceae and Dipterocarpaceae. The dominant presence of Myrtaceae members may be related to their genetic and adaptability factors (Yulisma et al 2018).…”
Section: Diversity Of Plant Speciessupporting
confidence: 84%
“…However, unfortunately, the peat swamp ecosystem in Aceh is highly threatened (Djufri et al 2016). Several studies identified the major factors affecting peat swamps in Aceh and Indonesia, including deforestation, land conversion to palm oil plantations and settlements, and fire forests during the dry season (Muchlisin et al 2015a;Thomy et al 2018;Ruysschaert and Hufty 2020). These factors have triggered a marked decline in the area's natural germplasm wealth, leading to a significant reduction in biodiversity.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular characteristics based on DNA barcoding in Tristaniopsis have rarely been studied. Studies focused on Myrtacease have involved one or two species of this genus [15,27,28]. The previous studies that focused only on Tristaniopsis and applied three barcoding markers found that only the ITS marker supported Tristaniopsis as a monophyletic genus [17].…”
Section: Introductionmentioning
confidence: 99%